A Phenomenological Study of Parental Involvement From Students’ Perspectives in Secondary Level English Learning in Nepal - Limbu, Chandra Bahadur (Academic Journal of Simara, 2026)
Parents’ involvement in learning English to their children is taken as a key factor. Parental involvement also fosters the academic achievement of their children. The study aims to explore the secondary-level English students’ perspectives regarding the involvement of their parents. The research questions of this study were how secondary-level students consider the involvement of their parents in learning English and in what ways they learn English with the support of their parents. The philosophical stance of the study is constructivism. This study used the phenomenological approach to explore the lived experiences of the students regarding the involvement of their parents in learning English. Semi-structured interviews and document analysis were used to collect the responses. And purposive sampling is adopted to select the 10 secondary-level students from the two government secondary schools. This study used thematic analysis for interpreting the qualitative data. The findings found that students were not only helped in learning English by their educated parents but also supported with learning materials. This study also revealed that the socioeconomic conditions of the students’ parents enhance their way of learning English.